Wakaf Tunai Sebagai Solusi Masalah Kemiskinan di Indonesia - Siti Kalimah Kalim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The economic growth of a country can be seen one of them is from the poverty level indicator. Poverty is the beginning of the damage and instability of the country's economy. Cash waqf is here to help solve this problem. Cash waqf has a general power where everyone can donate assets without certain limits. Cash waqf is also very strategic in creating jobs and reducing unemployment in selective production activities according to the rules of Shari'ah and benefit. Waqf has the potential to empower the real sector and strengthen economic fundamentals. By using cash waqf can help alleviate poverty which can be done by the Government through community empowerment programs. The goal is waqf in Indonesia to provide social welfare for the community, it is necessary to optimize waqf management by Nazirs. Cash waqf has tremendous economic potential to help the poor and alleviate poverty, especially considering that the majority of Indonesians are Muslim so that the amount of waqf funds that can be collected from certain communities is very large.